KAJIAN LITERATUR PERAN GURU DALAM MENINGKATKAN KEMAMPUAN LITERASI SISWA SEKOLAH DASAR - Tri Purwati; Chairunissa, Chairunissa; Okke Rosmaladewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine in depth the importance of teachers' roles in improving elementary school students' literacy skills through a literature review approach. Literacy is a fundamental and essential core competency in supporting student learning success. The method used is a literature review, reviewing various scientific sources, such as journals and relevant previous research. The results of the study indicate that teachers play a strategic role as facilitators, motivators, mediators, and innovators in literacy learning. Teachers who are able to plan engaging lessons, use appropriate strategies, and create a conducive literacy environment can improve students' reading, writing, and critical thinking skills. Therefore, improving teachers' pedagogical competence is a crucial factor in developing elementary school students' literacy.